Novel PAP-targeted CAR-T therapy enhances antitumor efficacy through CoupledCAR approach - Wei Ding; Xi Huang; Zhiyuan Cao; Chengfei Pu; Xianyang Jiang; Xiaogang Shen; Zhao Wu; Lei Xiao; Beibei Jia; Guiting Han; Wensheng Wang; Zhipeng Huang; et al. (Journal for ImmunoTherapy of Cancer)
Background The challenges that remain in the treatment of solid tumors with chimeric antigen receptor (CAR)-T cells include limited solid tumor-specific targets and poor CAR-T cell expansion and function due to limited availability of solid tumor antigens outside the tumor microenvironment. Prostate cancer is the second most common cancer among men worldwide. Current CAR-T therapies for prostate cancer lack specific targets, posing safety risks. To overcome these problems, we identified prostatic acid phosphatase (PAP, also known as ACPP or ACP3) as a feasible CAR-T target for prostate cancer and developed CoupledCAR, a novel approach for expanding tumor-targeting CAR-T cells without tumor antigens.Methods We analyzed the expression of PAP from The Cancer Genome Atlas database and validated its expression in normal and cancer tissues through immunohistochemistry staining. To generate anti-PAP specific antibodies, we screened the human single-chain antibody library using transmembrane PAP-His antigen and selected antibodies based on their binding ability and specificity. We constructed PAP-targeted CAR and evaluated their antitumor efficacy both in vitro and in vivo. We validated the function of PAP CoupledCAR in both in vitro and in vivo experiments, and further analyzed its mechanism using single-cell RNA sequencing (scRNA-Seq).Results PAP was specifically expressed in prostate epithelial and prostate cancer cells, with no expression in other tissues. Seven single-chain variable fragments were screened from the human single-chain antibody library, with S5D1 showing the highest binding ability for the PAP. PAP CAR-T cells demonstrated strong antitumor efficacy both in vitro and in vivo. Furthermore, the CoupledCAR system significantly expanded PAP CAR-T cells, promoting memory-like status, reducing exhaustion, and enhancing their antitumor efficacy. The scRNA-Seq demonstrated that the expansion of PAP CAR-T cells in the CoupledCAR system is mediated by costimulatory signals and cytokine signals, rather than T-cell receptor signals.Conclusions Our study is the first to demonstrate that PAP is a specific target for CAR-T therapy in prostate cancer, both in vitro and in vivo. We developed the CoupledCAR platform technology for solid tumor CAR-T cell therapy, enabling the expansion of tumor-targeting CAR-T cells without requiring tumor antigens and thereby enhancing their functionality against solid tumors.